2020
DOI: 10.1088/1402-4896/ab43fa
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering of beryllium oxide by deuterium at various temperatures simulated with molecular dynamics

Abstract: The sputtering yield of beryllium oxide (BeO) by incident deuterium (D) ions, for energies from 10 eV to 200 eV, has been calculated for temperatures between 300 K and 800 K using classical molecular dynamics. First, cumulative irradiations are done to build up a concentration of D in the material, equal to the one experimentally measured, that varies from 0.12 atomic fraction (300 K -500 K) to 0.02 atomic fraction (800 K). After building up the concentration of D, non-cumulative irradiations are done to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Subsequently, these NOs were used in target calculations. Tests showed that the best representation of the target orbitals was obtained when all σ and π target molecular orbitals (MOs) were represented by 2 Π NOs and all δ target MOs by 2 Σ + NOs, as these gave the best vertical excitation energies (VEEs) consistent with the other existing calculations.…”
Section: Target Calculationsmentioning
confidence: 66%
See 1 more Smart Citation
“…Subsequently, these NOs were used in target calculations. Tests showed that the best representation of the target orbitals was obtained when all σ and π target molecular orbitals (MOs) were represented by 2 Π NOs and all δ target MOs by 2 Σ + NOs, as these gave the best vertical excitation energies (VEEs) consistent with the other existing calculations.…”
Section: Target Calculationsmentioning
confidence: 66%
“…However, beryllium oxide (BeO) can easily form as a surface layer on the beryllium wall due to oxidation from traces of atmospheric oxygen in the plasma [2,3] and can subsequently enter the plasma by sputtering from the ions in the plasma. Therefore, BeO and its positive and negative ions are expected to be present as impurities in the plasma and this provides the principal motivation for the work.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) 43 simulations are an established technique which can consider interactions on the atomic level. MD simulations, reaching from irradiation energies between tens of eV up to tens of keV, have been carried out on different materials to understand the effect of various surface configurations on sputtering, but also the evolution of the surface morphology as a function of fluence [44][45][46][47][48] . While the precise integration of atomic interaction in MD is a very fundamental approach, this, however, requires high computational resources and time.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling can be used at different scales to predict and anticipate how HI reacts with Be and BeO materials. At atomistic scale, the fundamental interactions of HI with Be materials are obtained with density functional theory (DFT) [7][8][9][10][11][12][13] or molecular dynamics (MD) [14][15][16][17][18]. The outputs of these atomistic simulations can then be used in higher scale methods such as reaction diffusion model [19] or kinetic Monte Carlo [16] that can be used to simulate migration and trapping of fuel in Be at experimental length and time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations led so far on the Be-O-H system either focus on Be only [7][8][9][10][14][15][16] or BeO [11,12,17,18]. However, Raman spectroscopy of JET plasma facing materials [20,21] shown inclusion of BeO in Be in codeposited layers.…”
Section: Introductionmentioning
confidence: 99%